Leaf energy balance modelling as a tool to infer habitat preference in the early angiosperms - Lee, Alexandra P.; Upchurch, Garland; Murchie, Erik H.; Lomax, Barry H. (Royal Society, 2015)
Despite more than a century of research, some key aspects of habitat preference and ecology of the earliest angiosperms remain poorly constrained. Proposed growth ecology has varied from opportunistic weedy species growing in full sun to slow-growing species limited to the shaded understorey of gymnosperm forests. Evidence suggests that the earliest angiosperms possessed low transpiration rates: gas exchange rates for extant basal angiosperms are low, as are the reconstructed gas exchange rates for the oldest known angiosperm leaf fossils. Leaves with low transpirational capacity are vulnerable to overheating in full sun, favouring the hypothesis that early angiosperms were limited to the shaded understorey. Here, modelled leaf temperatures are used to examine the thermal tolerance of some of the earliest angiosperms. Our results indicate that small leaf size could have mitigated the low transpirational cooling capacity of many early angiosperms, enabling many species to survive in full sun. We propose that during the earliest phases of the angiosperm leaf record, angiosperms may not have been limited to the understorey, and that some species were able to compete with ferns and gymnosperms in both shaded and sunny habitats, especially in the absence of competition from more rapidly growing and transpiring advanced lineages of angiosperms.